Creating Sustainable Urbanity in the Fringe The Periphery as an opportunity for future Centrality (L'architettura delle città - The Journal of the Scientific Society Ludovico Quaroni, 2014)
The focus of this research – Sustainable Urbanity in the Fringe – is in the strategies to transform infrastructural improvements for containing risk hazards generated by climatic and geographical conditions, particularly in informal settlements, into sustainable and culturally relevant urban environments, in particular in South America (Colombia and Brazil).